THE ROLE OF ERGONOMIC RESEARCH IN ENHANCING THE PERFORMANCE OF EDUCATIONAL STAFF THROUGH PREVIOUS STUDIES - Naceur Djellali (International Journal of Innovative Technologies in Social Science, 2025)
This paper focuses on the application of ergonomics in the educational field by emphasizing the role of ergonomic design in enhancing the educational performance of all participants in the educational process as an integrated system. The focus is placed on several areas, such as the design of educational programs and curricula, instructional design, and the evaluation of educational performance, among others. The study also highlights the role of educational and school ergonomics based on the general system, which revolves around the design of school buildings and the physical environment in which they are located, due to its impact on the performance of the participants in the educational process. Particular attention is given to teacher performance, such as classroom design and equipment, as well as student behavior in daily activities, especially their interaction with school bags, including their weight and its impact on overall health, particularly back pain and musculoskeletal disorders.